PENGELOLAAN KEINGINAN MEROKOK DENGAN PENYULUHAN METODE 4Ds DI KELURAHAN PORIS JAYA PADA MASA PANDEMI - Umara, Annisaa Fitrah; Juliati, Siska; Antoni, Tresna Dinullah; Wulandari, Sri; Fitria, Niska; Nopiyanah, Siti; Indrianisa, Yulia; Mariani, Siska; Wijoyo, Eriyono Budi (Universitas Muhammadiyah Tangerang, 2022)
Cigarettes contain thousands of components that are harmful to health. In addition to its content, the hazardous materials in cigarettes are also produced from the process of planting, processing, and serving. Smoking also causes various health problems. However, information about cigarettes is not widely known by its users. Cigarettes are consumed by various age groups with varying frequency. In RW 07, there are many people who smoke and there is no smoking corner. The purpose of this community service is to increase the knowledge and awareness of participants about the dangers of smoking and how to manage the desire to smoke. The method used was a blended system for 6 participants who attend face-to-face. Counseling was given in the form of lectures, watched video, discussions, pre and posttests, as well as leaflet distribution. The results showed that there was an increase in participants' knowledge with an average pre-test score of 90 to 9.67. In conclusion, after being given counseling, there was an increase in participants' knowledge about the dangers of smoking and how to manage the desire to smoke. The next community service suggestion is to practice training in managing the desire to smoke as well as support from religious leaders and family members who want to quit smoking.